The Old Testament or Hebrew Bible in Africa: Challenges and prospects for interpretation and translation - Mojola, Aloo Osotsi (Verbum et ecclesia, 2014)
The Old Testament or Hebrew Bible is much loved in Africa. It is however encountered almost exclusively in translation, either through translation into local indigenous languages or translation into foreign, non-local languages. The source language Hebrew text is inaccessible to the vast majority of readers, including Christian pastors or theological students who would naturally be expected to have access by virtue of their profession. Knowledge of the Old Testament or Hebrew Bible is thus mediated through existing translations and interpretations, and through the popular or scholarly writings of Old Testament or Hebrew Bible experts. In many parts of Africa the latter are in very short supply. This article is an attempt to engage and critically reflect further on some of the issues arising out of this situation with specific reference to the work of Knut Holter, as well as others. This situation and the challenges posed for a full and unencumbered encounter with the Hebrew scriptures and prospects for the future is explored.Intradisciplinary and/or interdisciplinary implications: It is expected that the translation of the Hebrew scriptures involves interaction with local cultures and belief systems opening space for new interpretations from the perspectives of local world views and practices. The challenges for local Christian theologies and Christian doctrine in general arising from this are unavoidable.